Role of subjective norms in shaping entrepreneurial intentions among students - Nessel Karolina; Kościółek Szczepan; Leśniak Anna (Economics and Business Review)
In view of the inconsistency in prior research, the main goal of this analysis is to determine the influence of subjective norms on entrepreneurial intentions among Polish students. The secondary goal is to examine how these subjective norms are affected by entrepreneurial experiences among individuals close to students, the students’ self-employment history and work experiences, and their gender. Based on the framework of the theory of planned behaviour and data generated through surveys of students in a management programme (N = 255), structural equation modelling is applied. The results indicate that subjective norms indirectly influence students’ entrepreneurial intentions (through attitude towards entrepreneurship and perceived behavioural control). Regarding the antecedents of subjective norms, students’ prior entrepreneurial experience and work history are not significant, nor is gender. The entrepreneurial experience of individuals close to students has a significant and positive impact on subjective norms only when students are convinced of the successes of their close entrepreneurs.